1997
DOI: 10.1099/00221287-143-1-175
|View full text |Cite
|
Sign up to set email alerts
|

A 10.3 kbp Segment from nprB to argJ at the 102 Region of the Bacillus Subtilis Chromosome

Abstract: The approximately 10 kbp region encompassing nprB and argJ at 102" on the Bacillus subtilis chromosome was sequenced, revealing 12 ORFs, four known genes (argJ, argC, ipi and nprB) and two genes, yitV and yitS, whose products respectively display significant homology with L-gulono-y-lactone oxidase of rat and dihydrofolate reductase of Staphy/ococcus aureus. The data also indicated that nprB mapped to a different position than previously published.Keywords : Bacillus subtilis, genome sequencing, 102' region, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The reported sequences for these genes were found to be identical to our sequence, except for one position in sbcD (an additional G at position 1332 in our sequence) and two positions in wprA (T at position 11012 and C at position 11026 in our sequence instead of C and A, respectively). From these results and our previous data (Levine et al , 1997; Roche et al , 1997) we deduced that addA was located 53·5 kbp from argj. Consequently, in agreement with these results, its position on the B. subtilis genetic map has been remapped at 98° (Biaudet et al , 1996) instead of 86° indicated previously (Anagnostopoulos et al , 1993).…”
Section: Abbreviationsupporting
confidence: 81%
See 1 more Smart Citation
“…The reported sequences for these genes were found to be identical to our sequence, except for one position in sbcD (an additional G at position 1332 in our sequence) and two positions in wprA (T at position 11012 and C at position 11026 in our sequence instead of C and A, respectively). From these results and our previous data (Levine et al , 1997; Roche et al , 1997) we deduced that addA was located 53·5 kbp from argj. Consequently, in agreement with these results, its position on the B. subtilis genetic map has been remapped at 98° (Biaudet et al , 1996) instead of 86° indicated previously (Anagnostopoulos et al , 1993).…”
Section: Abbreviationsupporting
confidence: 81%
“…This completes our sequencing of the 54 kbp addA-argJ chromosomal region which proved to be much shorter than originally estimated. The sequencing strategy mainly involved Long Range PCR between addA and yisP (Roche et al , 1997), shotgun analysis after nebulization and subcloning in pUC18, as described previously (Levine et al , 1997). The gaps were filled by normal PCR.…”
Section: Abbreviationmentioning
confidence: 99%
“…Over 180 bp, there was 63.3% homology to the pho P gene of Bacillus subtilis [11]. Across 170 bp of the third clone there was 65.4% identity to the ntr A gene which codes for a Pseudomonas putida sigma factor [5], while the fourth clone had 58.6% identity over 140 bp to a B. subtilis npr B gene [6]. The final two clones had significant homology to the dtx R gene which regulates toxin production in Corynebacterium diphtheriae [1].…”
mentioning
confidence: 99%
“…Over 180 bp, there was 63.3% homology to the phoP gene of Bacillus subtilis [11]. Across 170 bp of the third clone there was 65.4% identity to the ntrA gene which codes for a Pseudomonas putida sigma factor [5], while the fourth clone had 58.6% identity over 140 bp to a B. subtilis nprB gene [6]. The ¢nal two clones had signi¢cant homology to the dtxR gene which regulates toxin production in Corynebacterium diphtheriae [1].…”
mentioning
confidence: 99%